Stability and Degradation Kinetic of l-tetrahydropalmatine under Stress Conditions of Temperature, Humidity, UV Light, pH, and Gastrointestinal Fluids - Dung, Pham Thi Phuong; Thuy, Pham Thi; Linh, Nguyen Tran; Tung, Nguyen Thach (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
l-Tetrahydropalmatine (l-THP) is an alkaloid with potential application in anti-addiction treatment. However, the stability profile and degradation kinetics of l-THP have not been comprehensively explored for product development. This study was conducted to evaluate the solid-state and solution stability of l-THP in accordance with ICH guidelines and to characterize its degradation kinetics under various stress conditions. The solid-state stability of l-THP was investigated under accelerated thermal conditions (50 °C, 70 °C, and 90 °C), various moisture-protective storage conditions, and light exposure. The stability of l-THP in solution was evaluated under photolytic stress, oxidative stress, different pH conditions, and simulated gastrointestinal fluids. The results showed that solid-state l-THP was unstable when exposed to elevated temperature, humidity, and light. Temperature caused drug degradation followed a first-order Arrhenius kinetic model (type 3). Under high-temperature (40 ± 2°C) and high-humidity (75 ± 5%) storage conditions, the degradation of l-THP followed second-order kinetics. l-THP solutions also turned yellow and showed a reduction in drug content upon light exposure. Rapid oxidative degradation was observed in the presence of a strong oxidizing agent (30% hydrogen peroxide), with degradation following first-order kinetics. In addition, l-THP exhibited low stability in strong acidic media (1.0 M HCl), neutral to slightly alkaline conditions (pH 6.8), and simulated intestinal fluids. In these media, drug degradation followed second-order kinetics. Palmatine was identified as the major degradation product of l-THP in solution under oxidative, pH-dependent, and gastrointestinal stress conditions. These findings provide a scientific basis for proposing appropriate storage conditions, supporting formulation development, and establishing quality criteria for pharmaceutical preparations containing l-THP.